Pembelajaran Bahasa Inggris untuk Anak Usia Dini Melalui Media Pembelajaran Instruksional Pocket Bee - Naufal Fachrur Rozi (JournEEL, 2022)
Aiming at finding the detailed scheme of teaching English to young learners through Pocket Bee instructional media, this scientific article scrutinizes Pocket Bee’s basis concept, Pocket Bee’s way of implementing, and young learners’ responses toward Pocket Bee. This scientific article was used qualitative method with descriptive qualitative as the research design. The subjects of this scientific article were well-filtered through convenience sampling with its inclusive sampling on young learners’ range of age. Twenty young learners of Lembaga Pendidikan As Salim (Ponpes/TPQ/RA/PAUD) were contributed to the entire process of teaching English to young learners through Pocket Bee instructional media. The researcher of this scientific article concludes that Pocket Bee is a TEYL instructional media in a form of interactive and child familiar design (i.e. bee form) that is created by the researcher in a purpose of providing young learners an instructional media that is able to maximize the possibility of enhancing young learners’ English proficiency. The implementation can be formed into five main steps on its main activity, namely (1) giving prior knowledge, (2) letting all students roll the dice, (3) picking picture card from the pocket bee, (4) testing students’ understanding, and (5) instructing all students to draw and to write down the picture card. The students' response agrees that Pocket Bee instructional media is capable to provide young learners a fun and happiness during the learning process because the scale of positive respondents reach out 100%. Those responses were validated by legal representative of Lembaga Pendidikan As Salim (Ponpes/TPQ/RA/PAUD).